2008
DOI: 10.1097/01.aud.0000305157.83012.f4
|View full text |Cite
|
Sign up to set email alerts
|

Normal Ipsilateral/Contralateral Asymmetries in Infant Multiple Auditory Steady-State Responses to Air- and Bone-Conduction Stimuli

Abstract: Objectives: Two-channel recordings of infants' airand bone-conduction auditory brainstem responses to brief tones show ipsilateral and contralateral (to the stimulated ear) asymmetries which may be used to isolate which cochlea is the primary contributor to the response. The objective of this study was to determine whether similar ipsilateral/contralateral asymmetries are also present in the air-and boneconduction "brainstem" (77 to 101 Hz) auditory steady-state responses (ASSRs) of infants.Design: Two-channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
35
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 31 publications
16
35
1
Order By: Relevance
“…In case of monaural stimulus presentation, the ipsilateral ASSR source is then more strongly activated than the contralateral source (Herdman et al 2002), resulting in stronger ipsilateral scalp recorded responses. This is consistent with previous ASSR studies reporting smaller or even absent 80 Hz ASSRs contralateral to the stimulus (Poelmans et al 2012;Small and Stapells 2008;van der Reijden et al 2005).…”
Section: Discussionsupporting
confidence: 82%
“…In case of monaural stimulus presentation, the ipsilateral ASSR source is then more strongly activated than the contralateral source (Herdman et al 2002), resulting in stronger ipsilateral scalp recorded responses. This is consistent with previous ASSR studies reporting smaller or even absent 80 Hz ASSRs contralateral to the stimulus (Poelmans et al 2012;Small and Stapells 2008;van der Reijden et al 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Contralateral AC masking was presented via insert earphones at the same intensity as the BC stimulation. The appropriate amount of clinical masking for BC stimuli in infants is not currently known, but a recent study has reported interaural attenuation for BC ASSR in infants to be higher than in adults, with at least 10-30 dB attenuation across 0.5-4 kHz [15].…”
Section: Ac and Bc Assrmentioning
confidence: 99%
“…Another recent study by Small and Stapells investigated the ipsi/contralateral asymmetries in BC ASSR recordings in infants younger than 11 months of age [15]. The findings indicated significantly larger asymmetries for infants than for adults, with individual infants exhibiting at least 10-30 dB of interaural attenuation for BC ASSR compared to no more than 10 dB in adults.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations